Agents and rules for the negotiation of interoperability solutions - Santos, T.; Coutinho, C.; Cretan, A.; Jardim-Goncalves, R. (Proceedings of the IEEE International Technology Management Conference & 19th ICE Conference (ICE 2013), 2013)
Competitiveness in the specialised and diversified global markets keeps pushing enterprises to abandon their traditional product centrism and instead concentrate their efforts in very narrow specialisation fields, relying on networks of other providers that are able to fulfil their needs towards the development of complete solutions. In that vision, given the heterogeneity of the globalised collaborations and the constant demand for change, innovation, and compliance to more exigent rules, it becomes very difficult for enterprises to cope with the pace of change. This paper proposes the implementation of a framework based on agents and rules to achieve solid and stable integration of solutions, via the use of a strong and formal negotiation mechanism. This negotiation will be the basis for increasing the enterprise interoperability in the supply chain for the development of solutions.